2005
DOI: 10.1590/s0100-879x2005000300019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sapindus trifoliatus on hyperalgesic in vivo migraine models

Abstract: Phytotherapies have offered alternative sources of therapy for migraine and gained much importance in prophylactic treatment. Sapindus trifoliatus is a medium-sized deciduous tree growing wild in south India that belongs to the family Sapindaceae. The pericarp is reported for various medicinal properties. A thick aqueous solution of the pericarp is used for the treatment of hemicrania, hysteria or epilepsy in folklore medicine. We have investigated the antihyperalgesic effects of the lyophilized aqueous extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The results showed that antagonism to dopamine D2 might underlie the mechanism involved in the anti-hyperalgesic activity of the plant extract 57 .…”
Section: Anti-migraine Activitymentioning
confidence: 96%
“…The results showed that antagonism to dopamine D2 might underlie the mechanism involved in the anti-hyperalgesic activity of the plant extract 57 .…”
Section: Anti-migraine Activitymentioning
confidence: 96%
“…However, so far no human trials have been reported with the use of Sapindus trifoliatus. [19][20][21] A wealth of literature lends to support the use of several herbal medicines in the treatment of migraine and other types of headache. Cannabis (Cannabis sativa), Ginger (Zingiber officinale) and Sweet bay (Laurus noblilis) are not to be excluded from the list.…”
Section: Sapindus Trifoliatus and Other Herbal Remediesmentioning
confidence: 99%
“…It is also beneficial for skin disorders like eczema and psoriasis (Arulmozhi et al, 2004[ 4 ]). In addition, Sapindus species has also been used for thousands of years in traditional medicine to treat excessive salivation, epilepsy, chlorosis, and neuroleptic diseases (Arulmozhi et al, 2005[ 3 ]). Current biological and pharmacological updates on Sapindus trifoliatus have been reviewed below (Table 1 (Tab.…”
mentioning
confidence: 99%
“…Current biological and pharmacological updates on Sapindus trifoliatus have been reviewed below (Table 1 (Tab. 1) ; References in Table 1: Arul et al, 2004[ 1 ]; Arulmozhi et al, 2004[ 2 ][ 4 ], 2005[ 3 ][ 5 ]; Bera et al, 2019[ 6 ]; Bodhankar et al, 1974[ 7 ]; Borad et al, 2001[ 8 ]; Chaudhary et al, 2019[ 9 ]; Chen et al, 2019[ 10 ]; Desai, et al, 1986[ 11 ]; Dixit and Gupta, 1982[ 12 ]; Gandreddi et al, 2015[ 13 ]; Grover et al, 2005[ 14 ]; Hu et al, 2018[ 15 ]; Kamboj and Dhawan, 1982[ 16 ]; Lal et al, 1976[ 17 ]; Lu et al, 2016[ 18 ]; Polli et al, 2021[ 19 ]; Pore et al, 2010[ 20 ]; Porsche et al, 2018[ 21 ]; Samiksha et al, 2019[ 22 ]; Sirisha et al, 2018[ 23 ]; Tiwari et al, 2008[ 24 ]; Tungmunnithum et al, 2018[ 25 ]; Wei et al, 2021[ 26 ]).…”
mentioning
confidence: 99%